2011
DOI: 10.1097/qad.0b013e3283471e89
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ recent thymic emigrants are infected by HIV in vivo, implication for pathogenesis

Abstract: We demonstrated that RTEs are effectively HIV infected. The similar infection rate observed in RTEs and other naive T cells, its relationship with plasma IL-7 levels, together with the lack of correlation between RTE infection and either thymic or peripheral proliferation, strongly suggests that RTE infection occurs either late during thymopoiesis or early on during their extrathymic maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…This finding indicates that quantification of viral DNA alone is not necessarily predictive of the size of the inducible latent reservoir and suggests caution in labeling a cellular reservoir of latent HIV-1 as "major" based solely on the frequency of infection. In addition to the memory CD4 ϩ T cell subsets, HIV-1 DNA is almost always detected in T N cells in both viremic and suppressed individuals, although with a much lower frequency than in the T CM and T TM compartments (6,7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Interestingly, in 2013 Saez-Cirion et al reported that in some HIV-1-infected individuals who received ART within 10 weeks of primary infection, viremia could be controlled for at least 24 months posttreatment interruption (8).…”
Section: A Latent Hiv-1 Reservoir Is Established In Resting Cd4mentioning
confidence: 99%
“…This finding indicates that quantification of viral DNA alone is not necessarily predictive of the size of the inducible latent reservoir and suggests caution in labeling a cellular reservoir of latent HIV-1 as "major" based solely on the frequency of infection. In addition to the memory CD4 ϩ T cell subsets, HIV-1 DNA is almost always detected in T N cells in both viremic and suppressed individuals, although with a much lower frequency than in the T CM and T TM compartments (6,7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Interestingly, in 2013 Saez-Cirion et al reported that in some HIV-1-infected individuals who received ART within 10 weeks of primary infection, viremia could be controlled for at least 24 months posttreatment interruption (8).…”
Section: A Latent Hiv-1 Reservoir Is Established In Resting Cd4mentioning
confidence: 99%
“…However, CDR3 diversity in T SCM is reduced during aging and, in the absence of cognate epitopes, T SCM persistence depends heavily on homeostatic proliferation (mediated through IL-7, IL-15, or IL-21) and the differentiation of scarce T RTE 11 . An increase in IL-7 levels was further correlated to the loss of naive 64 and CD4 T RTE cells 65 , which are both predictive of poor HIV prognosis [64][65][66] . Furthermore, co-infection with HCV presents an additional burden that contributes to the loss of T RTE 67 .…”
Section: Discussionmentioning
confidence: 92%
“…As most naïve Tregs are generated in the thymus, they express high levels of CD31, which is a marker for recent thymic emigrants [ 30 , 37 ]. To understand whether the impairment on the recovery of the CD45RA + Tregs population was associated with lower thymic output, we quantified CD45RA + Tregs expressing high levels of CD31 (CD45RA + CD31 hi Tregs), which should reflect blood's Tregs most recently exported from the thymus [ 38 , 39 ]. We observed that the CD45RA + CD31 hi Tregs counts were consistently lower in HIV-infected patients with CD4 + T-cell counts less than 350 cells/μl, irrespective of their time on ART, in comparison to uninfected individuals (Fig.…”
Section: Resultsmentioning
confidence: 99%